The Influence of Financial Literacy, Financial Behavior, Religiosity and Risk on Financial Distress : Case of Millennial Generation During the Covid-19 - Maidani; Rinjani; Muhammad Rianto (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of financial literacy, financial behavior, religiosity and risk on financial distress in the millennial generation during the Covid-19 pandemic (Case Study in Bekasi City). In this study, quantitative and descriptive research methods are used where the Millennial Generation in the city of Bekasi is the object. In this study using purposive sampling technique and using a sample of 95 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 4.0. The results of this study indicate that 2 X variables consisting of Financial Literacy and Financial Behavior have an influence on Financial Distress in the Millennial Generation during the Covid-19 pandemic (a case study in the city of Bekasi). As for the other 2 X variables, namely Religiosity and Risk, it has no influence on Financial Distress in the Millennial Generation during the Covid-19 pandemic (case study in the city of Bekasi). This study has a limited object of research that only uses 95 Millennial Generation in the city of Bekasi as research respondents. This is used as a suggestion for future researchers.